Multi-hop Routing in Wireless Sensor Networks An Overview, Taxonomy, and Research Challenges - Rani, Shalli; Ahmed, Syed Hassan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This brief provides an overview of recent developments in multi-hop routing protocols for Wireless Sensor Networks (WSNs). It introduces the various classifications of routing protocols and lists the pros and cons of each category, going beyond the conceptual overview of routing classifications offered in other books. Recently many researchers have proposed numerous multi-hop routing protocols and thereby created a need for a book that provides its readers with an up-to-date road map of this research paradigm. The authors present some of the most relevant results achieved by applying an algorithmic approach to the research on multi-hop routing protocols. The book covers measurements, experiences and lessons learned from the implementation of multi-hop communication prototypes. Furthermore, it describes future research challenges and as such serves as a useful guide for students and researchers alike. .
Preface -- Acknowledgment -- 1 Introduction -- 2 Multi-hop Energy Efficient Routing -- 3 Multi-hop Reliability and Network Operation Routing -- 4 Multi-hop Network Structure Routing Protocols -- 5 Future Research and Scope -- References -- Glossary. .
Keywords: Telecommunication; Computer networks .; Application software; Communications Engineering, Networks; Computer Communication Networks; Computer and Information Systems Applications